Development and Evaluation of Simulation-Problem–Based Learning for Sex Education. Issue 1 (January 2016) - Kim, Miok; Shin, Minho
Abstract : Nurses often encounter clients with sexual problems. A sexual problem is complicated and affects the quality of the client's life, and proper care requires the nurse to understand a variety of sex-related issues. Therefore, effective sex education for nursing students is necessary to prepare them for potential challenges from the client's sexual problems. In this study, we developed a simulation-problem–based sex education program for nursing students. The program immerses the students in a sex-related clinical situation to train them with nursing assessment, intervention skills, patient safety, patient privacy, and communication skills. To evaluate the effect of the program on the student's sexual knowledge and attitude, we provided the experimental group with simulation-problem–based sex education program along with traditional lectures, whereas the control group received only lectures. As a result, there were statistically significant differences in the improvement of knowledge ( P < .05) and attitude ( P < .05) of the two groups. The results show that the designed program effectively promotes nursing students' sexual knowledge and sexual attitude, and the simulation-problem–based learning is a practical and systematic approach to the sex education of nursing students.